Generating of cotidal dataset by spatial interpolation techniques / Khadijah Sahdan, Syed Ahmad Qusoiri Syed Abdul Karim and Othman Mohd Yusof - Khadijah, Sahdan; Syed Ahmad Qusoiri, Syed Abdul Karim; Othman, Mohd Yusof (2015)
Tidal observation is the main requirement in depth reduction to a specific vertical datum thus ensuring safe navigation prerequisite is met. The determination of water level (e.g. highest astronomical tide and mean sea level) can be achieved through tidal analysis which is crucial for the application of hydrographic and sustainable coastal development. Due to severity of the site conditions and resource constrains, not all areas can be represented just by one tidal station dataset. Significance changes in tidal characteristic from one location to another limit the application of single tide station to represent an entire observed area. Previously, it was recommended that series of tide stations were erected to properly represent and justify the reliability of the tidal data over the entire observed area. However, this approach requires great resources in providing multiple tide stations. Therefore an alternative approach in the estimation of tidal data; which is the concept of cotidal data needs to be introduced in order to provide tidal dataset. This is due to the fact that cotidal datasets does not require physical tide gauge to be positioned at a location as well as the need for observing tide data for a long period of time. Interpolation techniques are required in cotidal approach by analysing tidal data from multiple tide station networks. Typically, a number of real observed tidal data are used in generating the cotidal data. However, to further the cost-effective measures, real observed tidal data were being replaced with predicted tidal data published by Malaysian Navy. Therefore, this paper evaluates the reliability of cotidal data generated through predicted tides instead of real observed tide. A comparative study of the tide levels between real observed tides against cotidal data through statistical analysis was conducted. Three interpolation techniques were carried out at two locations of the coastal of Peninsular Malaysia as testing grounds. Final analysis will indicate the best interpolation method based on acceptable limits drawn by the International Hydrographic Organization (IHO). The application of cotidal will definitely save in terms of time; cost and effort to acquire reliable tide information especially for hydrographic and sustainable coastal development.